2022
DOI: 10.1101/2022.02.25.22271454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of the BNT162b2 vaccine among children 5-11 and 12-17 years in New York after the Emergence of the Omicron Variant

Abstract: Importance: There is limited evidence on the effectiveness of the BNT162b2 vaccine for children, particularly those 5-11 years and after the Omicron variant's emergence. Objective: To estimate BNT162b2 vaccine effectiveness against COVID cases and hospitalizations among children 5-11 years and 12-17 years during December, 2021 and January, 2022. Design: Analyses of cohorts constructed from linked statewide immunization, laboratory testing, and hospitalization databases. Setting/Participants: New York Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
75
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 12 publications
4
75
1
Order By: Relevance
“…Recent research suggests that vaccines may be less effective against omicron. Consistent with our results, an unpublished study in New York, 13 found that the vaccine effectiveness of BNT162b2 for the prevention of Covid-19 and hospitalization decreased from 66-51% and from 85-73% for children aged 12-17 years, respectively. The drop was more considerable among children 5 to 11 years; protection against Covid-19 fell from 68-12%, and protection against hospitalization fell from 100-48%.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Recent research suggests that vaccines may be less effective against omicron. Consistent with our results, an unpublished study in New York, 13 found that the vaccine effectiveness of BNT162b2 for the prevention of Covid-19 and hospitalization decreased from 66-51% and from 85-73% for children aged 12-17 years, respectively. The drop was more considerable among children 5 to 11 years; protection against Covid-19 fell from 68-12%, and protection against hospitalization fell from 100-48%.…”
supporting
confidence: 90%
“…The drop was more considerable among children 5 to 11 years; protection against Covid-19 fell from 68-12%, and protection against hospitalization fell from 100-48%. 13 Results among adults tell the same story. Early data from South Africa reported that BNT162b2 protection against Covid-19 related hospitalization decreased from 93-70% among adults.…”
mentioning
confidence: 80%
See 3 more Smart Citations